(untitled) (المؤتمر الدولي للتعليم الإلكتروني وتكنولوجيا المعلومات, 2025)
The accelerated integration of artificial intelligence (AI) into academic research workflows is reshaping foundational scholarly practices, particularly in the domains of academic writing, peer review, and research evaluation. Emerging evidence demonstrates that large language models (LLMs) and generative AI technologies have significantly enhanced linguistic fluency, syntactic coherence, and structural clarity in scholarly communication—benefiting especially researchers operating in multilingual or non-native English contexts. Concurrently, AI-enabled systems are being adopted to support peer review processes and to automate elements of research assessment, offering improvements in operational efficiency and evaluative consistency. Nevertheless, these developments are accompanied by critical ethical and epistemological concerns, including algorithmic opacity, potential amplification of bias, and the dilution of academic authorship and accountability. To address these complex dynamics, this study employs a dual-method research design, integrating a systematic literature review with thematic content analysis, to examine current frameworks for AI adoption in academic contexts. The findings underscore both the transformative potential and the inherent risks associated with AI-enabled research practices, highlighting the imperative for governance structures that are ethically robust, context-sensitive, and transparent. The paper concludes by offering strategic recommendations for institutions and stakeholders, aimed at fostering the responsible, equitable, and sustainable integration of AI technologies in academic research. Ultimately, the study argues for a balanced approach wherein AI augments—rather than supplants—human scholarly judgment and intellectual rigor.